Effect of Contrast Level and Image Format on a Deep Learning Algorithm for the Detection of Pneumothorax with Chest Radiography - Yoon, Myeong Seong; Kwon, Gitaek; Oh, Jaehoon; Ryu, Jongbin; Lim, Jongwoo; Kang, Bo kyeong; Lee, Juncheol; Han, Dong Kyoon (Journal of Digital Imaging, 2023)
Under the black-box nature in the deep learning model, it is uncertain how the change in contrast level and format affects the performance. We aimed to investigate the effect of contrast level and image format on the effectiveness of deep learning for diagnosing pneumothorax on chest radiographs. We collected 3316 images (1016 pneumothorax and 2300 normal images), and all images were set to the standard contrast level (100%) and stored in the Digital Imaging and Communication in Medicine and Joint Photographic Experts Group (JPEG) formats. Data were randomly separated into 80% of training and 20% of test sets, and the contrast of images in the test set was changed to 5 levels (50%, 75%, 100%, 125%, and 150%). We trained the model to detect pneumothorax using ResNet-50 with 100% level images and tested with 5-level images in the two formats. While comparing the overall performance between each contrast level in the two formats, the area under the receiver-operating characteristic curve (AUC) was significantly different (all p < 0.001) except between 125 and 150% in JPEG format (p = 0.382). When comparing the two formats at same contrast levels, AUC was significantly different (all p < 0.001) except 50% and 100% (p = 0.079 and p = 0.082, respectively). The contrast level and format of medical images could influence the performance of the deep learning model. It is required to train with various contrast levels and formats of image, and further image processing for improvement and maintenance of the performance.
Keywords: 5-level; Chest radiography; Contrast level; Deep learning; Image format; Joint photographic experts group; Learning models; Performance; Pneumothorax; Test sets; Algorithms; Deep Learning; Humans; Pneumothorax; Radiography; Radiography, Thoracic; Retrospective Studies; ROC Curve; Artificial intelligence; Contrast level; Deep learning; Image format; Pneumothorax